L1 Literacy Practices’ Impact on L2 Text Organization - Sayidina, Aisha (Emerging Trends in Education, 2019)
Situated within the Intercultural Rhetoric (IR) framework, this study uses text linguistic analysis of Arab students’ English academic papers to investigate the transfer of the Arabic language instruction practices into ESL written texts. The analysis involves a comparison of surface linguistic features (syntactic relations and cohesive devices) in a corpus of Arab students and English-speaking students’ papers. Furthermore, the Arabic and English-speaking students completed surveys about the skills emphasized in their L1 classrooms. It is believed that the methods of writing instruction in Arabic, which are influenced by diglossia, are transferred into ESL written texts. The results show that the Arabic speaking and English-speaking students’ texts exhibit differences at the rhetorical level. The characteristics of the ESL texts are similar to Arabic native texts which suggest a transfer of L1 learned writing methods into L2 texts. The findings from the linguistic analysis and the data obtained from the surveys are discussed with reference to Arabic teaching methodology, diglossia, orality, and learning experience transfer from Arabic into English.